Conditions and experiences of a university social responsibility in the local environment of Poland (Economic and Political Thought, 2018)
The article discusses the issues of social function and responsibility ofa higher education institution in its direct local surroundings. Universitiesoperating in medium size and small towns are the point of reference so theyare mainly non-public universities and state-owned higher vocational schools.The choice is justified by the fact that apart from their educational activity,they create local elites and remain culture-creating centres. Their educationaloffer is determined by the local community needs, which means that the pathsof training and their level express the scope of a higher education institution’sresponsibility for the development of human capital, the region, competitivenessand attractiveness of the local labour market.
Keywords: higher education institutions, education, human capital, region